Overview of the Performance of PKU Muhammadiyah Palangka Raya Islamic (PKUM PR) Hospital With a Welfare Approach - Tovik Ismail Saleh; Sagiran Sagiran; Sri Sundari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
This study aims to determine the picture of hospital performance. PKU muhammadiyah Palangka Raya islamic (PKUM PR) hospital from the lens of Kemaslahatan. There are eighteen objectives assessed in six aspects of benefit orientation, namely 1) worship orientation, 2) internal process orientation, 3) learning orientation, 4) talent orientation, 5) consumer orientation, and 6) wealth orientation. Research using qualitative methods. Selection of informants using the key informant method. Qualitative analysis uses the triangulation method as one way of verifying research results. Based on the six benefit orientations used to measure performance, it shows that PKU Muhammadiyah Palangka Raya Islamic (PKUM PR) Hospital has provided sufficient benefits for stakeholders, labor, and the environment. However, there are some things whose implementation has not been carried out systematically and structured, especially because there is no Sharia compliance team and the Sharia Supervisory Board. This is a reference for recommendations for PKU Muhammadiyah Palangka Raya Islamic (PKUM PR) Hospital so that the sustainability of the organization is maintained and maintained by continuously providing benefits. Keywords: Benefit, Hospital, Performance